2010
DOI: 10.1080/10255840902911536
|View full text |Cite
|
Sign up to set email alerts
|

A computational tool for the probabilistic finite element analysis of an uncemented total hip replacement considering variability in bone–implant version angle

Abstract: In the present study, a probabilistic finite element tool was implemented to assess an uncemented total hip replacement including variability in bone-implant version angle. The Monte Carlo method was used with two different performance indicators: the bone maximum nodal von-Mises elastic strain and the bone volume (BV) percentage exceeding specified strain limits. Implant version, bone stiffness and load magnitude were the most sensitive parameters. The results were more consistent using percentage BV under sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In addition, further resources are needed if bone geometry and material uncertainties are to be considered, such as a substantial sample of bones, representative of the population. Implant material variability was found to be minimally sensitive in a previous study (Dopico-Gonzalez et al, 2009a) and hence it was neglected for the present study; some studies have suggested the use of strainbased failure criteria as fracture predictors (Wong et al, 2001;Kopperdahl, 1999;Schileo et al, 2007;Morgan and Keaveny, 2001;Bayraktar et al, 2004), similar to that adopted in the present work. It is assumed that the femur will break when a certain amount of bone suffers strains over a limit close to the yield strain, believed to be approximately 0.78%70.06 (Kopperdahl, 1999).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In addition, further resources are needed if bone geometry and material uncertainties are to be considered, such as a substantial sample of bones, representative of the population. Implant material variability was found to be minimally sensitive in a previous study (Dopico-Gonzalez et al, 2009a) and hence it was neglected for the present study; some studies have suggested the use of strainbased failure criteria as fracture predictors (Wong et al, 2001;Kopperdahl, 1999;Schileo et al, 2007;Morgan and Keaveny, 2001;Bayraktar et al, 2004), similar to that adopted in the present work. It is assumed that the femur will break when a certain amount of bone suffers strains over a limit close to the yield strain, believed to be approximately 0.78%70.06 (Kopperdahl, 1999).…”
Section: Discussionmentioning
confidence: 75%
“…The reference geometry was determined for the femur using MATLAB modules, as in a previous study (Dopico-Gonzalez et al, 2009a).…”
Section: Finite Element Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A Monte Carlo analysis was performed on a hip stem construct to evaluate the likelihood of instability or micromotion based on uncertainty in the bone material properties, body weight loading, implant size, and the region of contact [25]. Considering uncertainty in bone property, loading, and also component alignment in a hip stem construct, Dopico-Gonzalez et al applied probabilistic methods to find that the volume of strained bone was sensitive to the implant version angle, bone modulus, and applied load; good agreement was demonstrated for Monte Carlo and Latin hypercube sampling [26,27]. In a study evaluating the response of three femurs to two types of implants, one with a stem and one without a stem, Dopico-Gonzalez et al showed that micromotion in both implants was most sensitive to implant positioning parameters (Fig.…”
Section: Structural Reliabilitymentioning
confidence: 99%